2020
DOI: 10.1038/s41467-020-15517-0
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of ribosome shutdown by RsfS in Staphylococcus aureus revealed by integrative structural biology approach

Abstract: For the sake of energy preservation, bacteria, upon transition to stationary phase, tone down their protein synthesis. This process is favored by the reversible binding of small stressinduced proteins to the ribosome to prevent unnecessary translation. One example is the conserved bacterial ribosome silencing factor (RsfS) that binds to uL14 protein onto the large ribosomal subunit and prevents its association with the small subunit. Here we describe the binding mode of Staphylococcus aureus RsfS to the large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
41
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 73 publications
6
41
1
Order By: Relevance
“…During 3D classification of the 50S subunits we also noticed a substoichiometric extra density in the vicinity of uL14. This density was further improved by focussed classification ( Figure S4B) and identified as B. subtilis ribosomal silencing factor RsfS, bound in a position analogous to that observed previously on the 50S subunit (Brown et al, 2017;Khusainov et al, 2020;Li et al, 2015) (Figure S6A-E). This assignment is supported by mass spectrometry (Table S1) and retrospective inspection of the RqcH-pullout also revealed substoichiometric density for RsfS on the 50S subunit ( Figure S6C).…”
Section: Identification Of Rsfs In Complex With Rqch-50s Complexessupporting
confidence: 59%
See 1 more Smart Citation
“…During 3D classification of the 50S subunits we also noticed a substoichiometric extra density in the vicinity of uL14. This density was further improved by focussed classification ( Figure S4B) and identified as B. subtilis ribosomal silencing factor RsfS, bound in a position analogous to that observed previously on the 50S subunit (Brown et al, 2017;Khusainov et al, 2020;Li et al, 2015) (Figure S6A-E). This assignment is supported by mass spectrometry (Table S1) and retrospective inspection of the RqcH-pullout also revealed substoichiometric density for RsfS on the 50S subunit ( Figure S6C).…”
Section: Identification Of Rsfs In Complex With Rqch-50s Complexessupporting
confidence: 59%
“…This assignment is supported by mass spectrometry (Table S1) and retrospective inspection of the RqcH-pullout also revealed substoichiometric density for RsfS on the 50S subunit ( Figure S6C). RsfS prevents association of 50S and 30S subunits (Hauser et al, 2012;Khusainov et al, 2020;Li et al, 2015) and therefore its presence in our datasets may indicate that RsfS also plays a similar role during RQC, analogous to that of Tif6/eIF6 in eukaryotic RQC (Su et al, 2019) (Figure S6F). Curiously, in the RqcH pull-out dataset we observed formation of 50S disomes ( Figure S1B) containing RqcH, YabO and P-tRNA, i.e.…”
Section: Identification Of Rsfs In Complex With Rqch-50s Complexesmentioning
confidence: 80%
“…7 e). RsfS is known to prevent premature subunit association during diminished nutrient availability, a molecular mechanism mimicked by eIF6 in eukaryotes 24,25 . However, in mitoribosomes, as shown in human, the RsfS homolog alone is not able to prevent subunit association and the anti-subunit association activity can only be achieved in the presence of mt-SAF32 and mt-LAF9.…”
Section: Intersubunit Sidementioning
confidence: 99%
“…structure discussed herein to model K + and mentioned that the densities that can be attributed to solvent molecules have been interpreted as Mg 2+ (Khusainov et al 2020). As a result, the 6SJ6 model deposited to the PDB contains 3 K + , 56 Mg 2+ and no water molecules.…”
mentioning
confidence: 92%
“…Sometimes, equivalent strategies are used during the refinement of cryo-EM structures and lead similarly to some deficient ion placement. In a recently published 50S Staphylococcus aureus cryo-EM structure at 3.2 Å resolution (PDBid: 6SJ6) 28 , the authors reported to have used the Thermus thermophilus 6QNR structure discussed herein to model K + and mentioned that the densities that can be attributed to solvent molecules have been interpreted as Mg 2+ . As a result, the 6SJ6 model deposited to the PDB contains 3 K + , 56 Mg 2+ and no water molecules.…”
mentioning
confidence: 99%